PERAN PROFITABILITAS DALAM MEMODERASI KEBIJAKAN DIVIDEN DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN PADA SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2020-2022 - Romlani, Ucik; Wahyuni, Ika; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2024)
Every individual needs to have management in their activities to achieve their goals. Likewise, with organizations, management is needed to run the company well. This helps investors make investment decisions by assessing the value and state of the company as a whole. The consumer goods industry is exciting because all its products are always needed daily. This sector produces products that can support the entire community, such as food, drinks, medicines, and others. This study aimed to analyze and test the role of profitability in moderating dividend policy and corporate Social Responsibility (CSR) on firm value. The population in this study was the Consumer Goods Industry Sector, with 124 companies and a sample of 11 companies. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing were conducted using Structural Equation Analysis—partial Least Square (PLS-SEM). The results of research hypothesis testing using the Smart PLS 3.0 application show that dividend policy has a significant positive effect on firm value, Corporate Social Responsibility (CSR) has a negative but insignificant effect on firm value, profitability significantly moderates the impact of dividend policy on firm value, profitability does not considerably moderate Corporate Social Responsibility (CSR) on firm value